The Impact of Artificial Intelligence Adoption and Agility on Career performance - Haeranah; Asniwati; Irfan Setiawan; Maryadi; Taupan (LPPM Institut Bisnis dan Informatika Kesatuan, 2025)
The rapid advancement of artificial intelligence in the era of industrial revolution 4.0 has transformed work dynamics globally, yet its impact on individual work efficiency and career performance in developing regions, such as South Sulawesi, remains to be seen. This study investigates the influence of artificial intelligence adoption and agility on employees’ work efficiency and career performance in South Sulawesi. A quantitative approach was employed, involving a survey of 280 respondents from both private and public sectors using a 5-point Likert scale questionnaire. The variables examined were artificial intelligence adoption, agility, work efficiency, and career performance, with data analysed through path analysis using SmartPLS. The findings reveal that artificial intelligence adoption and agility significantly affect both work efficiency and career performance, directly and indirectly, with work efficiency acting as a mediating variable. Artificial intelligence adoption recorded a total effect of 0.406 on career performance, while agility contributed 0.361. Furthermore, work efficiency had a direct effect of 0.273 on career performance, underscoring its vital role in supporting career advancement. The study suggests that organizations should promote AI adoption and enhance employee agility through training and adaptive skill development.